Нерівноважна термодинаміка і викидонебезпечність вугільного пласта - Alekseev, A.D.; Feldman, E.P. (Publishing house "Academperiodika", 2012)
We present the theoretical description of the non-equilibrium thermodynamics of a gas-bearing coal bed and the estimation of the outburst hazard of coal beds.